Carbon–Carbon Bond Formation Mediated by an Iron(0)–Olefin Pincer Complex - Lincoln, Zachary S.; Hoffbauer, Melissa R.; Iluc, Vlad M. (Synthesis, 2025)
C–H functionalization is a highly appealing strategy for accessing complex molecular structures. Herein, we show that π-tethered pincer ligands can engage in C–H activation when coordinated to iron. These reactions result in C(sp2)–C(sp2) bond formation through oxidative coupling and β-hydride elimination/reductive elimination pathways with alkynes and isocyanides.
Keywords: low-valent iron; coupling; alkenes; alkynes; isocyanides